Correlating permeability with drainage layer thickness overlying dredged marine clay in consolidation - S.M. Johan, Siti Farhanah; Chan, Chee Ming (Penerbit UTHM, 2022)
Dredged marine clay (DMC) known to have low permeability as fine-grained soils. The reuse of DMC as construction material could be a sustainable approach. Therefore, this research aims to correlating the permeability with granular drainage layer thickness by overlaying DMC. Except sand, recycled granular materials (recycled pavement materials and palm oil clinker) used as drainage layer. Laboratory testing was performed to determine the engineering properties of all materials and large oedometer test for the consolidation. DMC are categorised as CH soils, while sand and palm oil clinker can be considered as well-graded except for recycled pavement materials as poor-graded gravel. The k-value of Lsc (control) placed at the bottom compared the others specimen with drainage layer due to its low permeability properties with the kave of 7.31 x 10-9 m/s. The thickness of granular materials at 100% had positioned on top of 50%. In conclusion, by increasing the thickness of drainage layer, the dissipation of water also increases and speed up the consolidation of DMC. Therefore, it can conclude that recycled granular by-products can be reuse as backfill materials for land reclaimed.